Numerical analysis of self-centering energy dissipation brace with arc steel plate for seismic resistance. Issue 125 (October 2019) - Huang, Hua; Zhang, Fantao; Zhang, Wei; Guo, Mengxue; Urushadze, Shota; Wu, Guochao
Abstract: A self-centering energy dissipation brace (SEDB) with an arc steel plate was designed to improve the seismic performance of a structure and reduce the residual structural deformation after an earthquake. Seven groups of self-centering energy dissipation brace models of arc steel plates with different configurations were established based on ABAQUS software. A method for calculating the internal forces, stiffness, yield displacement and yield load of a brace was derived and shows agreement with theoretical values. This brace shows a favorable hysteretic performance that corresponds to its full, flag-shaped hysteretic curve. The stiffness transition of various stages is smooth and stable. The maximum residual deformation of the component is 3.75 mm and decreases as prepressing of the disc springs is increased. The component's reset performance can be fully utilized to satisfy specific needs. The advised values for designing the energy dissipation components of an arc steel plate are described as follows: 1/250 of a radian, width of 50–80 mm and thickness of 20 mm. The damping force, damping displacement and brace stiffness of the SEDB can be adjusted by the structural parameters of the arc steel plate to satisfy the engineering requirements. Highlights: A self-centering energy dissipation brace (SEDB) with an arc steel plate is designed. Seven groups of self-centering energy dissipation brace models are established by ABAQUS. A method for calculating the internal forces, stiffness, yield displacement and yield load is proposed.